PTH-115 Comparison of immunogenicity of biosimilar infliximab and originator infliximab in children with inflammatory bowel disease in real life setting. (17th June 2017) - Wahid, A; Muhammed, R
Abstract : Introduction: Biosimilar Infliximab has been licensed in the UK since 2015 for use in children with Inflammatory Bowel Disease (IBD). The aim is to compare the immunogenicity and response to treatment and factors associated with it in patients with IBD on treatment with originator and biosimilar Infliximab. Method: We included all patients with Crohn's Disease (CD) and Ulcerative colitis (UC) who had anti-Infliximab antibodies measured between 2011–2016. Retrospective review of patient notes and laboratory results were conducted. Anti-Infliximab antibodies were requested by the clinician in charge based on clinical needs of the patients. Anti-Infliximab antibodies were measured using second generation ELISA test identifying both free and combined antibodies. Disease remission was assessed by Physician Global Assessment (PGA). Results: In total 145 patients (124 with CD and 21 with UC) were included. 86 patients were on Originator Infliximab (80 with CD and 6 with UC) and 59 patients (44 with CD and 15 with UC) were on biosimilar Infliximab. Biosimilar Infliximab used was CT-P13 (Remsima and Inflectra). For children with Crohn's disease median age, disease extent and the rate of perianal involvement were not different in patients receiving originator and biosimilar Infliximab. A similar proportion of patients with Crohn's disease (70% in the originator group and 77% in the biosimilar group) developed anti-Infliximab antibodies. Detailed characteristics of these patients and their treatment are in Table 1. Comparison of the results of children with ulcerative colitis was limited by the small number of children receiving originator Infliximab. Conclusion: Anti-Infliximab antibody formation occurs in a high proportion of patients receiving both originator and biosimilar Infliximab. Dose/frequency adjustment is needed for a good proportion of IBD patients on Infliximab treatment to achieve clinical remission. Rate of anti-Infliximab antibody formation and clinical remission are very similar in CD patients on originator and biosimilar Infliximab. Disclosure of Interest: A. Wahid: None Declared, R Muhammed Conflict with: Abbvie, MSD, Conflict with: Abbvie, Pfizer, Dr Falk pharma, Conflict with: Tillotts pharma, Takeda pharmaceuticals